Design and performance analysis of time and Wavelength Division Multiplexed Passive Optical Network (TWDM-PON) / Fazryda Zakaria - Zakaria, Fazryda (2017)
Recent years, enormous deployment of Passive Optical Network (PON) happened worldwide due to high demand of network operators to serve their customer's requirements. Operators are hoping for an improvement and capability in terms of bandwidths and service support. In addition, they required an enhanced performance of access nodes and supportive equipment connected to their current PON networks. The direction of PON evolution is a main key problem for the telecommunication commerce. In April 2012, The Full Service Access Network (FSAN) announce Time and Wavelength Division Multiplexing (TWDM) became one of superlative resolutions NG-PON2 implementation. Network operators deliberate TWDM-PON to have more advantages than other methods because it is not much of risk and troublemaking and more cheaper system as it reuses current components and technologies. In this project, a design of TWDM that meet the requirement of NG-PON2 constructed on International Telecommunication Union/ Telecommunication Standardization Sector (ITU-T) was proposed. The design achieves the minimum requirements of standard ITU-T G.989 and was simulated using Opti system Simulation Software. This project implements NG-PON2 systems at 4xlOGbps using four different wavelengths range 1596 - 1603 nm, fiber link of 40 km and varied the value of power optical splitter from 1:2,1:4,1:8, 1:16 and 1:32. The results indicate that the suitable number of customers that can be served for this TWDM network is 60 based on simulation result for received power is - 27.5 dBm, excess power margin of 12 dB and maximum fiber span of 100 km.